Evaluation of employment-support services for adults with autism spectrum disorder. (August 2018) - Nicholas, David B; Zwaigenbaum, Lonnie; Zwicker, Jennifer; Clarke, Margaret E; Lamsal, Ramesh; Stoddart, Kevin P; Carroll, Cynthia; Muskat, Barbara; Spoelstra, Margaret; Lowe, Katelyn
The employment rate among persons with autism spectrum disorder has been noted as unacceptably low. Employment-support services are increasingly linked to the potential for favorable job outcomes, yet little is known about employment-support practices and the outcome of these interventions. This mixed-methods study examined employment-support resources for persons with autism spectrum disorder. An online survey was completed by 137 senior clinicians or administrators in employment-support programs in Canada. Additionally, 122 follow-up interviews were conducted with individuals with autism spectrum disorder (n = 71) and their parents/caregivers (n = 51). Findings indicate that the quality and beneficial impact of employment-support services for adults with autism spectrum disorder may be more favorably perceived by employment-support personnel than by individuals with autism spectrum disorder and their families. Furthermore, employment-support personnel were more disparaging about autism spectrum disorder vocational support capacity within their community, compared to their own programs. Individuals with autism spectrum disorder and their families seek services that support both accessing and retaining employment. Capacity-building in employment support for youth and adults with autism spectrum disorder is recommended, based on a reported insufficiency of, and a lack of evidence guiding, existing services. Program recommendations and an emerging model for integrated vocational support in autism spectrum disorder are offered.